2007
DOI: 10.1002/pmic.200600584
|View full text |Cite
|
Sign up to set email alerts
|

Predicting peptides bound to I‐Ag7 class II histocompatibility molecules using a novel expectation‐maximization alignment algorithm

Abstract: The useful structural features of class II MHC molecules are rarely integrated into T-cell epitope predictions. We propose an approach that applies a novel expectation-maximization algorithm to align the naturally processed peptides selected by the class II MHC I-A(g7) molecule - focusing on the five MHC-specific anchor positions. Based on the alignment profile, log of odds (LOD) scores supplemented with the Laplace plus-one pseudocounts method are applied to identify the potential T-cell epitopes. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…30,31 The use of naturally processed peptides instead of synthetic peptides or phage display libraries for the identification of peptidebinding motifs to MHC II molecules have the main advantage that the peptides had been selected by the antigen-presenting cells during the antigen processing, where a number of cellular events influence peptide selection. 32 We sequenced 486 unique naturally processed DR8-bound peptides by MDLC-mESI-ITMS/MS. As expected, most proteins generating the ligands were from membrane compartments, including plasma membrane, golgi apparatus, endosomes, lysosomes, endoplasmic reticulum and secretion vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 The use of naturally processed peptides instead of synthetic peptides or phage display libraries for the identification of peptidebinding motifs to MHC II molecules have the main advantage that the peptides had been selected by the antigen-presenting cells during the antigen processing, where a number of cellular events influence peptide selection. 32 We sequenced 486 unique naturally processed DR8-bound peptides by MDLC-mESI-ITMS/MS. As expected, most proteins generating the ligands were from membrane compartments, including plasma membrane, golgi apparatus, endosomes, lysosomes, endoplasmic reticulum and secretion vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…Whether such peptides form a significant fraction of the repertoire of islet β cell epitopes that are targeted by diabetogenic T cells needs to be examined in finer detail. I-Ag7 binding motif as determined by the alignment results from the expectation-maximization alignment algorithm of Chang et al [27] and shown by WebLogo. Preferred amino acids from positions P1 to P9 are indicated by their one letter code.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we utilized the vast datasets of natural peptides to develop a computational program that efficiently predicts epitopes selected by diabetogenic class II MHC molecules [27]. This approach had several unique aspects: (i) only the naturally selected peptides isolated from APCs were used in the development of this algorithm; (ii) the physical and structural characteristics of the binding pockets were used to refine the preferred amino acid anchors; and (iii) hindering residues, i.e.…”
Section: Biochemical Structural and Functional Properties Of Diabetementioning
confidence: 99%
See 2 more Smart Citations